2016
DOI: 10.1111/cas.13086
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of GBS‐01 for advanced pancreatic cancer refractory to gemcitabine

Abstract: GBS‐01, an extract from the fruit of Arctium lappa L. is an orally administered drug rich in arctigenin, which has been reported to exert antitumor activity by attenuating the tolerance of cancer cells to glucose deprivation. We investigated the maximum tolerated dose of GBS‐01 based on the frequency of the dose‐limiting toxicities (DLTs) and pharmacokinetics in patients with advanced pancreatic cancer refractory to gemcitabine. GBS‐01 was given orally at escalating doses from 3.0 g (containing 1.0 g burdock f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…There was no overt toxicity in the 60 mg/kg group except the stimulus response at the administration location, but repeated subcutaneous injection of large doses of ARG can induce injury to the liver and biliary duct and strengthen the reaction to the stimulus caused by PEG in dogs. Masafumi Ikeda 44 has studied the pharmacokinetics of ARG in patients with advanced pancreatic cancer refractory to gemcitabine. The results showed that ARG in patients exists as arctigenin glucuronide (AGG), and second peaks of ARG and AGG were observed, indicating enterohepatic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…There was no overt toxicity in the 60 mg/kg group except the stimulus response at the administration location, but repeated subcutaneous injection of large doses of ARG can induce injury to the liver and biliary duct and strengthen the reaction to the stimulus caused by PEG in dogs. Masafumi Ikeda 44 has studied the pharmacokinetics of ARG in patients with advanced pancreatic cancer refractory to gemcitabine. The results showed that ARG in patients exists as arctigenin glucuronide (AGG), and second peaks of ARG and AGG were observed, indicating enterohepatic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Seven patients were received more than one couse (28days) of GBS-01 administration but disease progression was observed within the following 28 days (PD) and clinical response was not evaluated in three patients patients because administration was ceased before one course completion [ 15 ]. Association between lactate AUC or Cmax and progression free survival time and overall survival of patients was analyzed by Kaplan-Meiyer methods among of lactate high and low groups that were divided in to two by median of Cmax or AUC, but no significant difference was observed in two groups either in terms of progression free survival time or overall survival time ( S3 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…lappa (GBS-01). The results showed high bioavailability of AG after oral administration, a good safety profile, and promising clinical antitumor activity responses [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antitumor activity of this lignan has been studied widely. An oral drug, GBS-01, which contains high levels of arctigenin was found to have a beneficial effect on pancreatic cancer in a phase I clinical study ( Ikeda et al, 2016 ). Arctigenin selectively induced apoptosis by upregulating apoptosis-related genes, including Bax, Fas , and caspase in A549 cells ( Susanti et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%